The land agent, 1700-1920 - Tindley, Annie; Reilly, Ciarán; Rees, Lowri Ann (Scotland's land., 2018)
This book brings together leading researchers of British and Irish rural history to consider the role of the land agent, or estate manager, in the modern period. Land agents were an influential and powerful cadre of men, who managed both the day-to-day running and the overall policy direction of landed estates. As such, they occupy a controversial place in academic historiography as well as popular memory in rural Britain and Ireland. Reviled in social history narratives and fictional accounts, the land agent was one of the most powerful tools in the armoury of the British and Irish landed classes and their territorial, political and social dominance. By unpacking the nature and processes of their power, 'The Land Agent' explores who these men were and what was the wider significance of their roles, thus uncovering a neglected history of British rural society.